79.0k views
0 votes
How do dis problem? 6.4n-10=4.4n+6

1 Answer

3 votes

Simplifying

6.4n + -10 = 4.4n + 6

Reorder the terms:

-10 + 6.4n = 4.4n + 6

Reorder the terms:

-10 + 6.4n = 6 + 4.4n

Solving

-10 + 6.4n = 6 + 4.4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4.4n' to each side of the equation.

-10 + 6.4n + -4.4n = 6 + 4.4n + -4.4n

Combine like terms: 6.4n + -4.4n = 2n

-10 + 2n = 6 + 4.4n + -4.4n

Combine like terms: 4.4n + -4.4n = 0.0

-10 + 2n = 6 + 0.0

-10 + 2n = 6

Add '10' to each side of the equation.

-10 + 10 + 2n = 6 + 10

Combine like terms: -10 + 10 = 0

0 + 2n = 6 + 10

2n = 6 + 10

Combine like terms: 6 + 10 = 16

2n = 16

Divide each side by '2'.

n = 8

Simplifying

n = 8

-ur local skatergirl, Rin:)

User MGH
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.